SECURE NETWORK MONITORING - Коробейнікова, Тетяна; Мичуда, Леся; Лужецька, Наталія; Федорченко, Віра (SWorldJournal, 2023)
n the paper, the tasks of SIEM, EDR and NDR in the SIEM-EDR-NDR triad are formed, the role, idea and processes of each component of the triad are considered separately, appropriate improvements to already existing known processes are proposed, the role of